PERBAIKAN STABILITAS DINAMIK TENAGA LISTRIK DENGAN POWER SYSTEM STABILIZER (PSS) - Gusa, Rika Favoria (FORISTEK : Forum Teknik Elektro dan Teknologi Informasi, 2011)
Stability of electrical system is one of systemâ€™s characters that make some machines can operate together in one frequency even there are some interrupts in normal condition or make them back into previous condition either in new or old equilibrium. Some variables that have to be observed are angel of rotor Î´,Â  speed of rotor Ï‰, and voltage source of generator vt . In this paper, simulation was done in IEEE 14 bus system at steady state condition, dynamic condition and adding of PSS as a stability tool. The result was PSS could make the system became stable even in new point of equilibrium. Keywords : stability of electrical power system, PSS, angel of rotor.